The spectrum of femininity : a process of deconstruction - Thiruchandran, Selvy (New Delhi : Vikas Pub. House : Distributors, UBS Publishers' Distributors, 1998)
With special reference to social conditions of female in Jaffna, Sri Lanka.
Keywords: Women -- India -- Social conditions; Femininity; Discrimination in employment -- India